PENERAPAN APLIKASI MATHEMATICS MOVIE TERHADAP MINAT BELAJAR MATEMATIKA DAN KEMAMPUAN ANALOGI RESPONDEN - Saluky Saluky (UIN Siber Syekh Nurjati Cirebon, 2016)
AbstractMathematics is a field of study that has an important role to measure the ability of the student. Poor understanding of students in schools on the subject matter of mathematics due to lack of interest in studying mathematics and cognitive abilities of students in schools is not up to the ability to maximize the existing analogy to students. Student interest in learning mathematics is less than optimal, it is necessary to develop the ability to maximize student interest in learning math analogy. one way to increase student analogy using Media. Mathematical Movie is instructional media delivered by teachers in the classroom with multimedia. Media movie mathematics useful in mathematics, as in mathematics definitely need a medium of learning. Math media can increase the interest and ability to learn mathematics student analogy. The ability of this analogy is very important in the learning of mathematics, such as mathematics should involve penganalogian. This research is a quantitative research using experimental methods. The technique of collecting data using questionnaires and tests Multiple choice. Data analysis technique used is the correlation analysis, regression analysis and path analysis. Data analysis started with the analysis of figures obtained correlation correlation between the influence of interest in learning math mathematics magnitude movies 0.574 with a degree of relationship, the effects on the ability analogy films mathematics to 0.454 students with the level of relationships, and interest in learning mathematical . The calculation result of research using path analysis we concluded that there is a direct effect of the application of mathematics to the interests of the film in learning mathematics by 73%, the application of mathematics to the ability of the film analogy students 60.6% and interest in learning math analogy with the student's ability by 75% So that with the application of mathematical applications for the movie analogies can increase the interest and ability of the students in learning mathematics learning.Keywords: Movie Mathematics, Learning Interests, Ability Analogy